Correlation of Total Lymphocyte Count with CD4 Count in HIV/AIDS Patients - Sanjaya, Ardo; Sugiarto, Christine; Jonathan, Ronald (Universitas Kristen Maranatha, 2015)
HIV infection is a chronic infection of the immune system with a target of CD4 cells. Total lymphocyte count (TLC) can be done in resource-limited areas and are able to be used as a substitute to CD4 count. An increase in CD8 count can disturb the correlation between CD4 and TLC especially during the late clinical stage.Objective of this research is to find out the correlation of total lymphocyte count with CD4 count and to find out the influence of the clinical staging on the correlation of total lymphocyte count and CD4 count.This study is an observational, analytical and cross sectional study using the medical records of Klinik Teratai RSHS Bandung. The data is sorted according to the WHO clinical staging and are analyzed using Pearsonâ€™s correlation and Fisherâ€™s transformation with Î±=0.05. The results showed that TLC have a correlation with CD4 count in all stadiums (r: 0,501-0,684, p<0,01). There is no significant difference of the correlation coefficients between the clinical stages (p>0.05). There is a correlation between TLC and CD4 count on HIV infected patients and there is no significant decrease of correlation of TLC and CD4 count on HIV infected patients with worsening of the WHO clinical stages.Â Keywords: CD4 count, total lymphocyte count, HIV/AIDS